Interprofessional and collaborative practice in health teams in primary care in the city of Juazeiro, Bahia, Brazil (Brazilian Journal of Health Research, 2023)
Introduction:Collaborative and interprofessional practices are activities in which different health professionals carry out shared work in order to ensure comprehensive health care. Objective: To evaluate the availability and readiness for collaborative and interprofessional practices among Primary Health Care professionals in the city of Juazeiro, Bahia. Methods: This is a cross-sectional, observational, descriptive and quantitative study. The data collection involved the application of the Readiness for Interprofessional Learning (RIPLS). Results: 97 professionals participated in the study: doctors, nurses, dentists, psychologists, physical educator, physiotherapist, nutritionist and social worker. The total assessment obtained in the three RIPLS factors showed a statistically significant difference between health professionals. The mean score for physicians differed from nurses (p=0.02). The average scores were located in the comfort zone for all professional categories, revealing high availability for teamwork, as well as for collaboration and patient-centered care. Collaborative and interprofessional practices were identified among primary care professionals. Conclusion: In this regard, it becomes possible to re (situate) the patient and their needs in the centrality of the process of health services, aiming the strengthening and effectiveness of the health system in meeting the demands of users in the perspective of comprehensive care.
Keywords: Health services; Interprofessionality; Comprehensive health care